(untitled) (Studia Prawnicze / The Legal Studies, 1965)
An Association (corresponding to the Soviet trust) is an intermediate organizational stage between the ministry and state enterprise in the current system of the national economy management. Such a situation between fundamentally different subjects (an administrative body and economic unit) impacts on the legal nature of the Association itself and its bodies. There are three different types of bodies in the Association: the Association Director, the Board, and the Technical and Economic (research and technology) Council. These bodies have fundamental differences in the obligatory nature of their establishment, in the procedure of their appointment, in the scope of competence, and in the position on the external relations of the Association (in relations with enterprises grouped in the Association, with a higher authority and other government agencies). These differences specify the role of the individual bodies in the Association, their relationship and legal nature. The Director appointed and removed by a minister manages all the activities of the Association as a sole manager. Their powers are limited to a certain extent by the powers of the Association Board. The Board is an expert and advisory body that solves the main problems of the Association. The purpose of its establishment is to ensure that the enterprises grouped in the Association have an impact on the activities of this Association. Therefore, the Board includes the directors of the enterprise group ex officio. The Board is not a continuing body; at least once every three months, its members should take part in the meetings convened by the Association Director who presides over them. Decisions are taken by an ordinary majority vote and must be approved by the Association Director in order to be valid. The Charter of the Association may also authorize the Board to make decisions binding on the Association Director and enterprise. The Technical and Economic Council includes specialists, representatives of the scientific community, business and public figures invited by the Association Director. The Council establishment is caused by the increased economic tasks of the Association and specified by the Director’s decision. At the suggestion of the Director, the Council considers fundamental questions about the state and development of the sector of the national economy represented by the Association but does not make decisions. However, its evaluations and recommendations can be preparatory material for the adoption of the relevant resolutions by the other bodies of the Association. Under these conditions, only the Director and Board can be considered a body according to the administrative law. In fact, each of these bodies is a separate organizational unit and has its own tasks defined by law. However, they are fundamentally different: an independent body (in the sense that it has the right to issue binding documents) is the Director while the Board is an auxiliary body. It could be considered an independent body only to the extent that it would have (according to the Charter) decisive powers. The competence of each mentioned body is determined by the role that this body should play in the Association. Their structure is also connected with this role: unity of command or collegiality. However, their activities are determined by the common tasks of the Association and are closely interdependent. Organizational ties are also a guarantee of their cooperation. Only the Director is responsible for the Association activities. First of all, we have in mind an administrative and legal responsibility (resulting from the relationship of subordination, financial and disciplinary relations under administrative law), and then we mean a civil liability (based on the contractual relations). This is either personal responsibility (especially in the relations under administrative law) or the responsibility of the body (imposed on the Association itself). As well, only the Director represents the Association outside — in full when it comes to administrative and legal relations and with some restrictions when it comes to civil law relations. The legal nature of these bodies is determined by the nature of the Association itself. The essence of the Association did not crystallize in its final form in legislation and, as a consequence, in doctrine. The position of the Association in the organization of the national economy continues to be at the centre of the discussion on new methods of management and planning. However, we can already clearly see some trends which allow us to consider the Association as a specific type of state organizational units that differs from state enterprises and bodies. The Association has the distinctive features of both of them in their close relationship, and this is precisely the characteristic feature of the Association as a special entity of the state economic administration. Thus, the Director and the Board should be considered the bodies of this entity, each within its own competence. This does not deprive them of their “state” or “administrative” nature: after all, the Association as a whole is a state institution. At the same time, it indicates the unity of the Association structure and links the activities of the bodies with the Association powers. Thus, it emphasizes the position of the Association as a new type of the state institutions in the area of the socialist economy.